Changes in HIV-related behaviours over time and associations with rates of HIV-related services coverage among female sex workers in Sichuan, China. Issue 3 (13th March 2008) - Lau, J T F; Choi, K C; Tsui, H Y; Zhang, L; Zhang, J; Lan, Y; Zhang, Y; Wang, N; Cheng, F; Gu, J
Abstract : Objectives: To investigate changes in HIV-related behaviours among female sex workers (FSW) and associations with services coverage rates. Methods: Behavioural surveillance data from Sichuan, China, were analysed. A mapping exercise was conducted; FSW were recruited from randomly selected sex-work establishments in 19 sites in Sichuan, China, from 2003 (n = 7068), 2004 (n = 6875) and 2005 (n = 6833). Results: Site variations were substantial. The random effect pooled AOR comparing the prevalence of condom use with regular sex partners, possession of condoms, HIV-related knowledge, HIV antibody testing and services coverage rates in 2005 versus 2003 ranged from 1.42 to 20.35. The 95% CI of these pooled AOR all excluded 1.0; hence rejecting the null hypothesis that such OR were not different from 1.0. Most of the AOR of these evaluative parameters (indicator of improvement) for the 19 individual sites in 2004 and 2005 (vs 2003) were significantly associated with coverage rates (Spearmen correlation coefficients  =  0.35 to 0.67, p<0.05). Conclusions: Improvements were observed in relevant behaviours and coverage rates and the two were associated with each other.